Christine [videorecording (DVD)] - Carpenter, John, 1948-; Gordon, Keith, 1961-; Stockwell, John, 1961-; Paul, Alexandra; King, Stephen, 1947- (Columbia TriStar Home Video, 1987)
She was born in Detroit on an automobile assembly line. But she is no ordinary automobile. Deep within her chassis lives an unholy presence. She is Christine, a red and white 1958 Plymouth Fury whose unique standard equipment includes an evil, indestructible vengeance that will destroy anyone in her way.